Finance and Development, June 1986. (Finance and Development; Finance and Development, 1986)
The global trade negotiations and use of fiscal measures to stimulate savings in developing countries are discussed. The four main elements of the global trading system likely to be at issue in the new round include nondiscrimination and the distinction between border and nonborder measures. Capital markets in developing countries are small, and the scope for diversification of financial institutions and financial instruments or assets is limited. The distinction between border and nonborder measures is blurred in the increased international concern with so-called unfair trade practices.